2021
DOI: 10.1111/ped.14760
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for growth hormone treatment in Japanese children

Abstract: Background: There are not clear evidence to date evaluating patients' and caregivers' preferences for the recombinant-human growth hormone (r-hGH) injection in children in Japan. This study aimed to quantitatively evaluated the factors driving preferences for daily r-hGH injections among Japanese children with growth hormone deficiency (GHD) or their caregivers and to determine the relative importance of treatment delivery factors. Methods: This study was performed among Japanese children with GHD or their car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…As might be expected from a treatment regimen that results in reduced life interference, most patients/caregivers in the study preferred the somatrogon injection schedule, reporting it as being more convenient and easier to follow compared with the Somatropin injection schedule. Similar sentiments have been reported from patient preference studies in the United States [ 12 ] and Japan [ 18 ], in which patients showed a strong hypothetical preference for a treatment schedule with less frequent injections compared with once-daily regimens. The importance of the injection schedule to patients was also highlighted in both studies, which found it to be the most important treatment-related factor assessed [ 12 , 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…As might be expected from a treatment regimen that results in reduced life interference, most patients/caregivers in the study preferred the somatrogon injection schedule, reporting it as being more convenient and easier to follow compared with the Somatropin injection schedule. Similar sentiments have been reported from patient preference studies in the United States [ 12 ] and Japan [ 18 ], in which patients showed a strong hypothetical preference for a treatment schedule with less frequent injections compared with once-daily regimens. The importance of the injection schedule to patients was also highlighted in both studies, which found it to be the most important treatment-related factor assessed [ 12 , 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…Although the somatrogon group had a higher incidence of injection-site pain compared with the Genotropin group, subjects may prefer to receive 1 injection of somatrogon compared with 7 injections of Genotropin during the course of a week. This is supported by a discrete choice experiment conducted in Japanese children with GHD, which found a clear preference for a onceweekly injection schedule instead of a once-daily injection schedule [13]. Although the use of once-weekly somatrogon may improve adherence among patients with GHD, it is possible that some patients with poor adherence to daily GH treatment (e.g., adolescents) will also show poor adherence to long-acting treatments such as once-weekly somatrogon.…”
Section: Discussionmentioning
confidence: 93%
“…This information is key because it can explain a smaller growth catch-up without the need for further investigation into other potential causes. In this regard, devices with a dose setting were the preferred choice among patients and caregivers in a recent study by Tanaka et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, detection of poor adherence to GH treatment can be problematic because patients/caregivers may be reluctant to admit to (or do not remember) missed doses and may overestimate their adherence to treatment during discussions with health care providers (HCPs) [ 4 ]. Devices that offer a dose-setting memory may therefore be beneficial in improving adherence [ 6 ]. In addition, with prevalence estimates of nonadherence ranging from 5% to 82% [ 5 ], it is difficult to compare adherence rates among studies due to the variability in methods used to evaluate and define adherence [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%